2017
DOI: 10.1007/s12094-017-1669-3
|View full text |Cite
|
Sign up to set email alerts
|

Utility of urinary circulating tumor DNA for EGFR mutation detection in different stages of non-small cell lung cancer patients

Abstract: The study demonstrated the feasibility of using transrenal DNA in mutation profiling for different stages of NSCLC patients. It highlights the importance of continual monitoring and has potential clinical utility in the clinical management of NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…QC specializes in cfDNA extraction, and many researchers have reported its efficient purification performance [17][18][19]. The QC has also been widely used for liquid biopsy using urinary cfDNA in various urologic and non-urologic malignancies [5,[28][29][30]. The MM utilizes a magnetic bead-based extraction method.…”
Section: Discussionmentioning
confidence: 99%
“…QC specializes in cfDNA extraction, and many researchers have reported its efficient purification performance [17][18][19]. The QC has also been widely used for liquid biopsy using urinary cfDNA in various urologic and non-urologic malignancies [5,[28][29][30]. The MM utilizes a magnetic bead-based extraction method.…”
Section: Discussionmentioning
confidence: 99%
“…Togneri et al reported that urinary cfDNA of UBC patients has a higher tumor genomic burden and greater detection potential as a genomic biomarker (90%) than urinary pellet DNA (61%). Moreover, some researchers have reported that circulating cfDNA in the blood of patients with advanced cancer was filtrated through glomeruli and detected in urine as “trans‐renal cfDNA.” Urinary cfDNA may have the potential to allow observation of the sequential genetic change of UC, from detecting the disease at an early stage to monitoring the response of systemic therapy, even if there is no evidence of disease in the urinary tract …”
Section: Discussionmentioning
confidence: 99%
“…In non-urological cancers with urine liquid biopsy, mutation rate rather than methylation and integrity was mainly studied. EGFR and KRAS mutations in NSCLC, [17][18][19][20] KRAS and TP53 mutations in colorectal cancer, 13,21,22 EGFR mutations in gastric cancer, 23 and in other cancers have been reported, but not for PDAC. Chen et al reported that the concordance rate of EGFR mutations in NSCLC patients between tissue and ucfDNA was 88%.…”
Section: Discussionmentioning
confidence: 99%